Classification, mechanism and surgical treatments for spinal canal cysts. Issue 1 (December 2016) - Sun, Jianjun
Abstract A variety of cystic lesions may develop in spinal canal. These cysts can be divided into intramedullary, intradural, extradural, cervical, thoracic, lumbar, and sacral cysts according to anatomical presentation, as well as arachnoid, meningeal, perineural, juxtafacet, discal, neurenteric cysts, and cyst-like lesions according to different etiologies. Mechanisms of initiation and growth vary for different cysts, such as congenital, trauma, bleeding, inflammatory, instability, hydrostatic pressure, osmosis of water, secretion of cyst wall, and one-way-valve effect, etc. Up to now, many treatment methods are available for these different spinal canal cysts. One operation method can be applied in cysts with different types. On the other hand, several operation methods may be utilized in one type of cyst according to the difference of location or style. However, same principle should be obeyed in surgical treatment despite of difference among spinal canal cysts, given open surgery is melely for symptomatic cyst. The surgical approach should be tailored to the individual patient.